If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + 3(x + -1) = 24 Reorder the terms: 15 + 3(-1 + x) = 24 15 + (-1 * 3 + x * 3) = 24 15 + (-3 + 3x) = 24 Combine like terms: 15 + -3 = 12 12 + 3x = 24 Solving 12 + 3x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 3x = 24 + -12 Combine like terms: 12 + -12 = 0 0 + 3x = 24 + -12 3x = 24 + -12 Combine like terms: 24 + -12 = 12 3x = 12 Divide each side by '3'. x = 4 Simplifying x = 4
| 19+13z=9+12z | | 4b^2-5b+1=0 | | 2/5x+3=4(7/8+1x/12) | | (y+9)(y+1)=0 | | 13-7x=52-14x | | (8+u)(2u+9)=0 | | 287/6/11 | | X^2+12x+120=0 | | -2(w-1)(-w-4)=0 | | X^2+12x+120=o | | 13+10x=53-24x | | 282/6/11 | | x^2+60=0 | | (4y-3)+y=y+(5-y) | | (7-2)/5 | | f(x)=5x^2-7 | | (3+3)(3+3)= | | 3(p-10)/4p | | -1/5x^2=0 | | 5/16+6=5/4 | | 61+4x=9x+22 | | -5=4+a+(-3) | | 22=10+w+4 | | Y=x^2-4x+5 | | -7+p+9=-2 | | 3x-5x=18 | | d+6+(-8)=4 | | 8/y-6/y2 | | y=9x-8y-8x | | (3)/(x+1)=(9)/(4x-5) | | (3)/(x+1)=(9)/(4x+5) | | k+36=28 |